First report of the benthic dinoflagellate, Gambierdiscus belizeanus (Gonyaulacales: Dinophyceae) for the east coast of Sabah, Malaysian Borneo - Chui, P.L; Po, T.L; Toh, H.T; Tuan‐Halim, T.N; Cheng, K.W; Ng, B.K; Usup, G. (Blackwell Publishing Asia, 2011)
Species of the genus Gambierdiscus Adachi & Fukuyo, toxicus Adachi & Fukuyo are known producers of neurotoxins associated with ciguatera fish poisoning (CFP). In this study live samples were collected from seaweed beds of the east coast of Sabah, Malaysian Borneo and a strain of Gambierdiscus was isolated and cultured. Examination of the thecal fine morphology was undertaken using light, epifluorescence, and scanning electron microscopy. Observed morphological features and their associated morphometric information enabled identification to Gambierdiscus belizeanus Faust. This represents the first report for the occurrence of G. belizeanus in the Asia Pacific region.